Pharmacokinetics of a single oral administration of two cannabidiol formulations in fed and fasted horses - Di Salvo, Alessandra; Bazzano, Marilena; Rocca, Giorgia della; Galarini, Roberta; Marchegiani, Andrea; Paoletti, Fabiola; Giusepponi, Danilo; Mantovani, Matteo; Laus, Fulvio (Frontiers in Veterinary Science, 2025)
Pain management in horses plays a pivotal role in the therapeutic approach to several diseases. Horses have cannabinoid receptors at the level of dorsal root ganglia, blood vessels, and synoviocytes that can be up or down- regulated by inflammatory conditions, justifying the possible efficacy of exogenous cannabinoids (i.e., phytocannabinoids) in managing several painful pathologies in this animal species. However, the current use of supplements containing cannabidiol (CBD) in equines is based on anecdotal evidence, without the support of sufficient pharmacokinetic studies. In humans, the concentration peak of CBD and the area under the concentration-time curve (AUC) are both strongly influenced by food administration. Also, in equids, the oral bioavailability of some drugs can be influenced by the meal but no information is available about CBD. This study investigated the pharmacokinetics of CBD following single oral administration of two different formulations of pure CBD (oil and paste), dosed at 1 mg/kg, at two different times about food administration. CBD oil and CBD paste were administered orally at 1 mg/kg to eight healthy horses according to a cross over design, and blood samples were taken at pre-fixed time-points for the pharmacokinetic analyses. The obtained pharmacokinetic data did not allow for statistically significant differences between formulations (paste or oil) and feeding time (fed and fasted status). However, following treatment with the paste, the Cmax was achieved in a shorter time range compared to the oily formulation, indicating that it could be a better formulation to consider in future equine studies.